Modellreaktionen zum Mechanismus der Asparaginase aus E. coli - K.H. Röhm; Fr. Schneider (CHIMIA)
A molecular mechanism for the reactions catalyzed by asparaginase (EC3.5.1.1) was proposed, the essential features of which are the participation of the α-carboxyl-group of the substrates in the catalytic process and the intermediate formation of aspartic acid anhydride. As a nonenzymatic model reaction following essentially the same mechanisms we found the hydrolysis of monoamides of 1,8-naphthalenedicarboxylic acid which is considerably facilitated by the neighbouring COOH-group. The kinetics of the formation of 1,8-naphthalenedicarboxylic acid anhydride from different monoamides and of the hydrolysis of the anhydrids as well as its formation from the acid was investigated. This reaction is an outstanding example of the efficiency of approximation and orientation in a COOH-catalyzed intramolecular amide hydrolysis. The rate of hydrolysis of 1,8-naphthalenedicarboxylic acid propylamide is more than two orders of magnitude greater than for phthalic acid monoamide.